Carbon nanocomposite material and method for preparing the same
Patent Information
- Application Number
- CN202611431676.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-15
- Publication Date
- 2026-10-20
AI Technical Summary
但现有产品存在两大关键痛点:一是易产生微裂纹等损伤,传统复合材料依赖非共价作用自修复,存在修复效率低、力学稳定性差的问题;二是废弃后难以降解回收,碳纳米组分与基体界面结合紧密,易造成资源浪费与环境污染
[0013]本发明的有益效果是:本发明材料光热自修复效果优异,力学恢复率90%-8%,可循环修复10-15次;碱性环境下碳纳米组分回收率85%-95%,可循环利用。改性碳纳米管与基体界面相容性好,显著增强材料力学性能。碳纳米管分散均匀,结合双动态键体系,结构稳定、导电性能佳、抗老化能力强,综合使用性能优良。
Smart Images

Figure FT_1 
Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional composite materials technology, specifically relating to a carbon nanocomposite material and its preparation method. Background Technology
[0002] Carbon nanocomposites are widely used in electronics, aerospace, and other fields due to their excellent mechanical and functional properties. However, existing products suffer from two major drawbacks: first, they are prone to damage such as microcracks, and traditional composite materials rely on non-covalent self-healing, resulting in low repair efficiency and poor mechanical stability; second, they are difficult to degrade and recycle after disposal, as the carbon nanoparticles are tightly bonded to the matrix interface, easily leading to resource waste and environmental pollution. Although some studies have improved material strength through static covalent bond modification, dynamic repair cannot be achieved; some self-healing materials lack environmentally friendly recycling designs, making it difficult to meet the needs of sustainable industrial development. Therefore, developing carbon nanocomposites that combine efficient self-healing and closed-loop recycling characteristics has become an urgent technical challenge to be solved in this field. Summary of the Invention
[0003] To address the aforementioned problems, this invention provides a carbon nanocomposite material and its preparation method. This material possesses photothermal self-healing and closed-loop recycling capabilities, exhibits excellent mechanical, electrical, and interfacial properties, and is suitable for applications in flexible electronics, aerospace, and other fields.
[0004] To achieve the above objectives, the present invention adopts the following technical solution: A carbon nanocomposite material, said composite material being prepared from the following raw materials in parts by weight: 2-8 parts modified carbon nanotubes, 40-60 parts monomers containing disulfide bonds, 35-55 parts monomers containing boron-oxygen bonds, 0.5-1.5 parts initiator, and 80-120 parts solvent; The composite material is formed by polymerizing the monomers containing disulfide bonds and the monomers containing boron-oxygen bonds through an initiator to form a polymer matrix; the carbon nanotubes are modified by amino / hydroxyl grafting and uniformly dispersed in the polymer matrix to form a carbon nanotube-double dynamic bond synergistic system.
[0005] Preferably, the monomer containing a disulfide bond is selected from one or more of diethyl 3,3'-dithiodipropionate, dimethyl 3,3'-dithiodipropionate, 3,3'-dithiodipropionic acid, and di(2-hydroxyethyl) disulfide.
[0006] Preferably, the boron-oxygen bond-containing monomer is selected from one or more of 4-vinylphenylboronic acid, triallyl borate, and phenylboronic acid.
[0007] Preferably, the initiator is one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and benzoyl peroxide.
[0008] Preferably, the solvent is one or more of N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone.
[0009] Preferably, after near-infrared light-triggered repair, the mechanical properties of the composite material recover at a rate of 90%-98%, and the number of repair cycles is 10-15; after decrosslinking in an alkaline aqueous solution, the carbon nanoparticle recovery rate is 85%-95%.
[0010] Preferably, the preparation method of the carbon nanocomposite material includes the following specific steps: S1. Mix carbon nanotubes with amino / hydroxylating agents and react at 60-80℃ for 4-6 hours to obtain amino / hydroxyl grafted modified carbon nanotubes. S2. Add the modified carbon nanotubes, monomers containing disulfide bonds, monomers containing boron-oxygen bonds and initiator to the solvent, and ultrasonically disperse for 10-20 minutes to form a mixture. S3. The mixture is polymerized in situ at 85-95°C for 2-4 hours under nitrogen protection, and then demolded after cooling to obtain carbon nanocomposite material.
[0011] Preferably, in step S1, the amino / hydroxylating agent is one or more of ethylenediamine, glycolic acid, ethanolamine, and alanine.
[0012] Preferably, in step S2, the ultrasonic power is 300-500W; in step S3, the heating rate of in-situ polymerization is 2-5℃ / min.
[0013] The beneficial effects of this invention are: the material exhibits excellent photothermal self-healing properties, with a mechanical recovery rate of 90%-8%, and can be cyclically repaired 10-15 times; the carbon nanotube component has a recovery rate of 85%-95% under alkaline conditions, making it recyclable. The modified carbon nanotubes have good interfacial compatibility with the matrix, significantly enhancing the material's mechanical properties. The carbon nanotubes are uniformly dispersed, combined with a double dynamic bond system, resulting in a stable structure, excellent electrical conductivity, strong anti-aging ability, and excellent overall performance. Attached Figure Description
[0014] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the embodiments of the invention to explain the invention and do not constitute a limitation thereof.
[0015] Figure 1 This is a line graph comparing the repair rate and tensile strength of different samples after 15 cycles. Detailed Implementation
[0016] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0017] Example 1: A carbon nanocomposite material of Example 1, the composite material is prepared from the following raw materials in parts by weight: 5 parts modified carbon nanotubes, 50 parts diethyl dithiodipropionate (a monomer containing disulfide bonds), 45 parts 4-vinylphenylboronic acid (a monomer containing boron-oxygen bonds), 1.0 part azobisisobutyronitrile (azobisisobutyronitrile), and 100 parts N,N-dimethylformamide (solvent). The preparation method of the carbon nanocomposite material in this embodiment includes the following specific steps: S1. Add carbon nanotubes to a three-necked flask, add concentrated nitric acid, reflux at 80°C for 4 hours, filter and wash until neutral; then add ethylenediamine and ethanol, react at 70°C for 5 hours, filter and vacuum dry to obtain amino-grafted modified carbon nanotubes with a grafting rate of 10%. S2. Add the modified carbon nanotubes, monomers containing disulfide bonds, monomers containing boron-oxygen bonds and initiator to the solvent, and ultrasonically disperse them at 400W power for 15 minutes to form a mixture. S3. Under nitrogen protection, the mixture was heated to 90°C at a heating rate of 3°C / min and polymerized in situ for 3 hours. After cooling, it was demolded to obtain a carbon nanocomposite material with a disulfide bond to boron-oxygen bond molar ratio of 1:1.
[0018] Example 2: A carbon nanocomposite material of Example 2, the composite material is prepared from the following raw materials in parts by weight: 2 parts modified carbon nanotubes, 40 parts diethyl dithiodipropionate monomer containing disulfide bonds, 35 parts 4-vinylphenylboronic acid monomer containing boron-oxygen bonds, 0.5 parts azobisisobutyronitrile initiator, and 80 parts N,N-dimethylformamide solvent. The preparation method of one carbon nanocomposite material in this embodiment is the same as that in Example 1.
[0019] Example 3: A carbon nanocomposite material of Example 3, the composite material is prepared from the following raw materials in parts by weight: 8 parts modified carbon nanotubes, 60 parts diethyl dithiodipropionate (a monomer containing disulfide bonds), 55 parts 4-vinylphenylboronic acid (a monomer containing boron-oxygen bonds), 1.5 parts azobisisobutyronitrile (azobisisobutyronitrile), and 120 parts N,N-dimethylformamide (solvent). The preparation method of one carbon nanocomposite material in this embodiment is the same as that in Example 1.
[0020] Comparative Example 1: A carbon nanocomposite material of Comparative Example 1, the composite material is prepared from the following raw materials in parts by weight: 5 parts modified carbon nanotubes, 50 parts diethyl dithiodipropionate monomer containing disulfide bonds, 1.0 part azobisisobutyronitrile initiator, and 100 parts N,N-dimethylformamide solvent; The preparation method of one of the carbon nanocomposites in this comparative example is the same as that in Example 1, except that no boron-oxygen bond-containing monomers are added.
[0021] Comparative Example 2: A carbon nanocomposite material of Comparative Example 2, the composite material is prepared from the following raw materials in parts by weight: 5 parts of unmodified carbon nanotubes, 50 parts of diethyl dithiodipropionate (a monomer containing disulfide bonds), 45 parts of 4-vinylphenylboronic acid (a monomer containing boron-oxygen bonds), 1.0 part of azobisisobutyronitrile (azobisisobutyronitrile), and 100 parts of N,N-dimethylformamide (solvent). The preparation method of one of the carbon nanocomposites in this comparative example is the same as that in Example 1, except that unmodified carbon nanotubes are used.
[0022] Performance testing 1. Photothermal response self-healing performance test Referring to GB / T1040.2-2006, the composite material was prepared into a Type 1A standard tensile specimen (150 mm in length, 10 mm in width, and 2 mm in thickness). Five parallel specimens were prepared for each test group and placed in an environment of 25℃ and 50%RH for 24 hours for later use. A utility knife (0.1 mm blade thickness) was used to score a crack along the width direction in the middle of each specimen. The crack length was controlled to be 5 mm and the depth to be 1 / 2 of the specimen thickness. After scoring, the consistency of crack size was confirmed by a stereomicroscope (20x magnification). The cracked sample is fixed on the stage, and a near-infrared laser is used to aim at the cracked area. The power density is set to 0.5-2W / cm2. During the irradiation, the temperature of the cracked area is monitored in real time with an infrared thermal imager (controlled at 50-80℃). One repair is completed after continuous irradiation for 5-15 minutes. Performance testing: After repair, the sample is left to stand for 1 hour at 25℃ and 50%RH. The tensile strength is then tested on a universal testing machine (tensile rate 5mm / min) according to GB / T1040.2-2006. The mechanical property recovery rate is calculated as "tensile strength after repair / initial tensile strength before repair × 100%". The "damage manufacturing - photothermal repair - performance testing" process is repeated 10-15 times for the same batch of samples. The mechanical property recovery rate is recorded after each cycle to evaluate the stability of the cyclic repair.
[0023] Table 1. Test data on the photothermal response self-healing performance of different samples.
[0024] 2. Closed-loop recycling performance test Take 10g of composite material sample and immerse it in 0.5-2mol / L sodium hydroxide / potassium hydroxide solution. Stir at 40-60℃ for 2-4h until the material is completely decrosslinked. Filter to separate the filtrate from the solid residue. Wash the residue with deionized water until neutral and vacuum dry at 80℃ for 4h. Weigh the mass of the dried solid and calculate "mass of recovered carbon nanotubes / mass of modified carbon nanotubes in raw materials × 100%" to obtain the carbon nanotube recovery rate.
[0025] Table 2. Closed-loop recovery performance test data for different samples
[0026] 3. Mechanical property testing Type 1A tensile specimens (150 mm in length, 10 mm in width, and 2 mm in thickness) were prepared according to GB / T1040.2-2006, and Type A notched simply supported beam impact specimens (80 mm in length, 10 mm in width, 4 mm in thickness, 2 mm in notch depth, and 45° in notch angle) were prepared according to GB / T1843-2008. Five parallel specimens were prepared for each performance test and placed in an environment of 25℃ and 50%RH for 24 hours for conditioning. Before testing, the universal testing machine (tensile test) and the simply supported beam impact testing machine were calibrated. The loading speed of the universal testing machine was calibrated to 5 mm / min, and the impact speed of the impact testing machine was calibrated to 3.5 m / s. Tensile property test: Clamp the tensile specimen in the chuck of the universal testing machine, ensuring that the specimen axis is consistent with the direction of force. Start the equipment and load at a rate of 5 mm / min. Record the maximum load and elongation at break when the specimen breaks. Calculate the tensile strength (maximum load / cross-sectional area of specimen) and elongation at break (elongation at break / gauge length of specimen × 100%) according to the formula. Impact performance test: Place the notch-down impact specimen on the support of the impact testing machine after conditioning, ensuring that the specimen and the support are in close contact. Start the pendulum to complete the impact test, record the impact absorbed energy, and calculate the impact strength of the simply supported beam according to the formula (impact absorbed energy / cross-sectional area at the notch of the specimen). For each performance index, remove the outliers (data that deviate from the average value by ±10%) from 5 parallel specimens, and take the arithmetic mean of the remaining valid data as the final test result.
[0027] Table 3. Test data of mechanical properties of different samples
[0028] 4. Conductivity test The composite material was processed into a cube sample with dimensions of 20mm × 20mm × 2mm. The upper and lower surfaces of the sample were successively sanded with sandpaper (800# → 1200# → 2000#) until smooth and flat, removing surface burrs. After cleaning with anhydrous ethanol, the sample was placed in an environment of 25℃ and 50%RH for 12 hours for conditioning. Before testing, the four-probe resistivity meter was calibrated, and a standard resistance element (with known resistivity) was selected for verification to ensure that the test error was ≤2%. Initial resistivity test: Place the conditioned sample on the stage of the four-probe tester, and make the four probes in close contact with the upper surface of the sample. Set the test pressure to 10N and the ambient temperature to 25℃. After the reading stabilizes, record the volume resistivity value (test 3 times and take the average value as the initial resistivity). Repair cycle treatment: Referring to the "Photothermal response self-healing performance test" method, the sample was subjected to 5 "damage-repair" cycles (after each scratch crack, it was irradiated with 808nm, 1W / cm2 near-infrared light for 10min for repair); after completing 5 repair cycles, the volume resistivity of the sample was tested again (the average value was taken from 3 tests); and the resistivity change rate was calculated. If the change rate was ≤15%, the conductivity function was stable.
[0029] Table 4. Test data of conductivity properties of different samples
[0030] 5. Anti-aging performance test According to GB / T16422.2-2014, the sample was placed in a xenon lamp aging test chamber (irradiance 0.71W / (m2·nm), blackboard temperature 65℃, relative humidity 50%) and aged for 1000h; after aging, the tensile strength and self-healing rate were tested, and the "performance after aging / performance before aging × 100%" was calculated. If the retention rate of both indicators is ≥80%, the environmental adaptability is qualified.
[0031] Table 5. Test data on the anti-aging performance of different samples
[0032] The data in the table above shows that: (1) Examples 1-3 (dual dynamic bond system) had an initial self-repair rate of 91%-95% and a 15-cycle repair rate of 84%-88%, which were significantly better than Comparative Example 1 (single disulfide bond system, initial 75%, 15-cycle 45%) and Comparative Example 2 (unmodified carbon nanotubes, initial 82%, 15-cycle 62%), indicating that the synergistic effect of disulfide bond and boron-oxygen bond can greatly improve repair efficiency and cycle stability; (2) The carbon nanoparticle recovery rate of the example is 90%-92%, which is higher than that of Comparative Example 1 (88%) and Comparative Example 2 (85%), confirming that the decrosslinking characteristics of the dual dynamic bond system are more conducive to the efficient recovery of carbon nanoparticle components; (3) The tensile strength of the example is 42-50 MPa and the impact strength is 10-12 kJ / m2, which is significantly improved compared with Comparative Example 1 (tensile strength 35 MPa, impact strength 8 kJ / m2) and Comparative Example 2 (tensile strength 38 MPa, impact strength 9 kJ / m2), reflecting the synergistic enhancement effect of double dynamic bonds and modified carbon nanotubes on mechanical properties; (4) The resistivity change rate after five repairs in Example 5 was 7.9%-8.2% (≤15%), while that in Comparative Example 2 reached 25%, indicating that the conductive network constructed by the modified carbon nanotubes was more stable. (5) The tensile strength and self-healing rate of the example after aging were 83%-86%, which is far greater than that of Comparative Example 1 (72%, 68%), proving that the double dynamic bond system has better weather resistance stability.
[0033] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A carbon nanocomposite material, characterized in that, The composite material is prepared from the following raw materials in parts by weight: 2-8 parts modified carbon nanotubes, 40-60 parts monomers containing disulfide bonds, 35-55 parts monomers containing boron-oxygen bonds, 0.5-1.5 parts initiator, and 80-120 parts solvent; The composite material is formed by polymerizing the monomers containing disulfide bonds and the monomers containing boron-oxygen bonds through an initiator to form a polymer matrix; the carbon nanotubes are modified by amino / hydroxyl grafting and uniformly dispersed in the polymer matrix to form a carbon nanotube-double dynamic bond synergistic system.
2. The carbon nanocomposite material according to claim 1, characterized in that, The monomer containing a disulfide bond is selected from one or more of diethyl 3,3'-dithiodipropionate, dimethyl 3,3'-dithiodipropionate, 3,3'-dithiodipropionic acid, and di(2-hydroxyethyl) disulfide.
3. The carbon nanocomposite material according to claim 1, characterized in that, The boron-oxygen bond-containing monomer is selected from one or more of 4-vinylphenylboronic acid, triallyl borate, and phenylboronic acid.
4. The carbon nanocomposite material according to claim 1, characterized in that, The initiator is one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and benzoyl peroxide.
5. A carbon nanocomposite material according to claim 1, characterized in that, The solvent is one or more of N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone.
6. A carbon nanocomposite material according to claim 1, characterized in that, After being repaired by near-infrared light, the mechanical properties of the composite material recovered at a rate of 90%-98%, and the number of repair cycles was 10-15. After decrosslinking in an alkaline aqueous solution, the recovery rate of carbon nanoparticles was 85%-95%.
7. A method for preparing a carbon nanocomposite material according to any one of claims 1-6, characterized in that, The specific preparation steps are as follows: S1. Mix carbon nanotubes with amino / hydroxylating agents and react at 60-80℃ for 4-6 hours to obtain amino / hydroxyl grafted modified carbon nanotubes. S2. Add the modified carbon nanotubes, monomers containing disulfide bonds, monomers containing boron-oxygen bonds and initiator to the solvent, and ultrasonically disperse for 10-20 minutes to form a mixture. S3. The mixture is polymerized in situ at 85-95°C for 2-4 hours under nitrogen protection, and then demolded after cooling to obtain carbon nanocomposite material.
8. The method for preparing a carbon nanocomposite material according to claim 7, characterized in that, In step S1, the amino / hydroxylating agent is one or more of ethylenediamine, glycolic acid, ethanolamine, and alanine.
9. The method for preparing a carbon nanocomposite material according to claim 7, characterized in that, In step S2, the ultrasonic power is 300-500W; in step S3, the heating rate of in-situ polymerization is 2-5℃ / min.